2022
DOI: 10.1039/d2cc00477a
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-rich sulfide/selenide cathodes for next-generation lithium-ion batteries: challenges and perspectives

Abstract: The extraordinarily high capacity exhibited by lithium-rich oxides has motivated intensive investigations towards both the cationic and anionic redox processes. With recent main focus on the anionic redox behavior, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…The results suggested that the smaller the RNT diameter, the more Ru atom d (i.e., Ru 4 d ) and chalcogen atom p (i.e., S 3 p and Se 4 p ) orbitals overlapped. [ 37–39 ] Interestingly, when the diameter was 1.5 nm, the orbitals overlapped almost 100%, indicating the strong spin–orbital interaction between the Ru and chalcogen atoms (Figure 3c). [ 40,41 ] In other words, the introduction of sufficient surface curvature can modify the electronic structures and bond identities.…”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that the smaller the RNT diameter, the more Ru atom d (i.e., Ru 4 d ) and chalcogen atom p (i.e., S 3 p and Se 4 p ) orbitals overlapped. [ 37–39 ] Interestingly, when the diameter was 1.5 nm, the orbitals overlapped almost 100%, indicating the strong spin–orbital interaction between the Ru and chalcogen atoms (Figure 3c). [ 40,41 ] In other words, the introduction of sufficient surface curvature can modify the electronic structures and bond identities.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, metallic selenides (such as ZnSe, CoSe 2 , and SnSe) are considered to be promising anode materials. Besides their high theoretical capacity, metallic selenides have higher electrical conductivity, weaker metal-selenium bonds, narrower energy gaps, and larger lithium-insertion interstitial sizes than metallic oxides and sul des, which accelerate the electron migration and the conversion reaction kinetics [11,12]. However, metallic selenides still suffer from huge volume changes, particle aggregation, and relatively low intrinsic conductivities during charge/discharge processes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) have come a long way in terms of energy density, endurance, and safety since their commercial debut in 1991. However, state-of-the-art LIBs are approaching their specific energy limits due to the intercalation feature of both the cathode and the anode. , The ever-increasing daily demand for electric vehicles and grid-scale energy storage calls for LIBs with higher energy density. On this very note, lithium metal batteries (LMBs) have returned to the limelight after decades of oblivion because of their low electrochemical potential (−3.04 V vs the standard hydrogen electrode) and superhigh theoretical specific capacity (3860 mA h g –1 ), which is 10 times higher than that of graphite anode. There is no doubt that the combination of high-capacity cathodes with higher charging voltage and Li metal anodes, such as Li metal with high-voltage LiCoO 2 (LCO), LiNi 0.8 Mn 0.1 Co 0.1 O 2 (NCM811), layered lithium-rich oxide, and LiNi 0.5 Mn 1.5 O 4 (LNMO), is an intriguing method to achieve a specific energy of 500 W h kg –1 . …”
Section: Introductionmentioning
confidence: 99%
“…However, state-of-the-art LIBs are approaching their specific energy limits due to the intercalation feature of both the cathode and the anode. 1,2 The ever-increasing daily demand for electric vehicles and grid-scale energy storage calls for LIBs with higher energy density. 3−5 On this very note, lithium metal batteries (LMBs) have returned to the limelight after decades of oblivion because of their low electrochemical potential (−3.04 V vs the standard hydrogen electrode) and superhigh theoretical specific capacity (3860 mA h g −1 ), which is 10 times higher than that of graphite anode.…”
Section: Introductionmentioning
confidence: 99%